Reflective learning journals for construction education - a case study - Baccarini, David (2004)
In recent years, journal writing has become an effective and widely used teaching and learning strategy which is popular with both students and lecturers in higher education. This paper provides a review of the literature of reflective learning journals, in particular: learning processes, types, uses, purposes, benefits and issues of implementation within an educational program. Using action research, the author describes the results of using learning journals within an undergraduate construction degree program. The key conclusions of the research were: students support the use of reflective journals for learning; reflective journals should be introduced early into the curriculum and developed gradually throughout the learning program; learners should be given instructions to facilitate the reflective learning process; and, journal structure and assessment support the reflective learning process.